Analysis of cooling curves obtained from the human corpses where time since death is known - Khaja Mohiddin, Shaik; Jaffar Hussain, A P; Kumar, Virendra; Subhedar, Abhijit; Taqiuddin Khan, Mohd (Journal of Indian Academy of Forensic Medicine, 2019)
A physical change that may occur in a corpse after death would be heat exchange from the body to the surrounding environment. An  attempt has been made by the investigators to analyse the cooling curves obtained from the human corpses where time since death is  known. A total of 100 human corpses selected for the study. The study was conducted in typical winter season from October to  December of the year 2013. During the process of recording, ambient temperature remains almost same on every day of the study  period and it was 27°C-28° C. On an average, it took18-20 hours for the thin built bodies to reach the ambient temperature, whereas 20- 22 hours for moderately built bodies and for thick built bodies 22-24 hours. The cooling curves obtained by applying observed data, is  of more or less double exponential sigmoid one. It is observed that the process of cooling retarded in its earlier stages, represented by a  flat portion in its upper most part, signifying the occurrence of a lag period in the earlier stages of cooling, known as "temperature  plateau". Followed by a plateau, the investigators observed that a steeper portion of the cooling curve having two different components  of variable lengths on the curve, representing different phases of cooling during the process of reaching the equilibrium with the  ambient temperature. The initial rate of cooling in most of the cases is to be 0.5ºC/hour rising to 1ºC/hour during the period of  maximum cooling. The average rate of cooling/hour has been estimated as 0.5ºC.
Keywords: Core Temperature; Conduction; Convection; Radiation; Temperature plateau